Hepatitis C virus infection among Brazilian hemophiliacs: a virological, clinical and epidemiological study - Carmo,R.A. (2002)
We determined and analyzed risk factors of hepatitis C virus (HCV)-infected Brazilian hemophiliacs according to their virological, clinical and epidemiological characteristics. A cross-sectional and retrospective study of 469 hemophiliacs was carried out at a Brazilian blood center starting in October 1997. The prevalence of HCV infection, HCV genotypes and factors associated with HCV RNA detection was determined. The seroprevalence of anti-HCV antibodies (ELISA-3.0) was 44.6% (209/469). Virological, clinical and epidemiological assessments were completed for 162 positive patients. There were seven (4.3%) anti-HCV seroconversions between October 1992 and October 1997. During the same period, 40.8% of the positive anti-HCV hemophiliacs had abnormal alanine transaminase (ALT) levels. Plasma HCV RNA was detected by nested-RT-PCR in 116 patients (71.6%). RFLP analysis showed the following genotype distribution: HCV-1 in 98 hemophiliacs (84.5%), HCV-3 in ten (8.6%), HCV-4 in three (2.6%), HCV-2 in one (0.9%), and not typeable in four cases (3.4%). Univariate analysis indicated that older age (P = 0.017) and abnormal ALT levels (P = 0.010) were associated with HCV viremia, while the presence of inhibitor antibodies (P = 0.024) and HBsAg (P = 0.007) represented a protective factor against the presence of HCV RNA. These findings may contribute to a better understanding of the relationship between HCV infection and hemophilia.